1992
DOI: 10.1093/nar/20.1.41
|View full text |Cite
|
Sign up to set email alerts
|

In vitrocleavage of double- and single-stranded DNA by plasmid RSF1010-encoded mobilization proteins

Abstract: We have used purified RSF1010 mobilization proteins to reproduce in vitro a strand-specific nicking at the plasmid origin of transfer, oriT. In the presence of Mg2+, the proteins MobA (78-kDa form of RSF1010 DNA primase), MobB, and MobC and supercoiled or linear duplex oriT DNA form large amounts of a cleavage complex, which is characterized by its sensitivity to protein-denaturant treatment. Upon addition of SDS to such a complex, a single strand break is generated in the DNA, and MobA is found linked to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
135
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(140 citation statements)
references
References 24 publications
5
135
0
Order By: Relevance
“…Relaxase proteins are also active in relaxosomes containing auxiliary DNA-binding proteins of host or plasmid origin. IncF, IncW, IncP, and IncQ systems offer well studied examples (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Among IncF plasmids factors known to stimulate nic cleavage include E. coli integration host factor and plasmid proteins TraM and TraY (22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…Relaxase proteins are also active in relaxosomes containing auxiliary DNA-binding proteins of host or plasmid origin. IncF, IncW, IncP, and IncQ systems offer well studied examples (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Among IncF plasmids factors known to stimulate nic cleavage include E. coli integration host factor and plasmid proteins TraM and TraY (22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…1. Plasmid RSF1010 contains its specific relaxase and oriT (Scherzinger et al, 1992). Mobilization of this plasmid by R6K and its derivatives was used to define the region carrying the relaxase of R6K and its accessory proteins.…”
Section: Mapping the Region Of R6k Involved In Conjugative Transfermentioning
confidence: 99%
“…published by Flashner et al (1996) can be interpreted as the proteins TaxA and TaxC (DDP1 and DDP2), but not TaxC alone, being able to cleave the nic site in vivo, inferring that both proteins will also be required for relaxation in vitro, as is also the case for other relaxases, such as TraI of RP4 (Pansegrau et al, 1990) or MobA of RSF1010 (Scherzinger et al, 1992) The insertion of the ⍀ cassette in plasmid pSU4746 introduces transcription and translation stop signals within taxA. In order to ascertain whether the mutation affected ᮊ 1997 Blackwell Science Ltd, Molecular Microbiology, 24, 1157-1168 Fig.…”
Section: Mapping the Region Of R6k Involved In Conjugative Transfermentioning
confidence: 99%
“…It has been reported that conjugative plasmids, which belong to different incompatibility groups from the group IncF of F and F-like plasmids, encode endonucleases which have other activities both in cleaving the singlestranded DNA at a specific site and in rejoining the cleaved products (Bhattacharjee & Meyer 1991;Scherzinger et al 1992;Pansegrau et al 1993). It has also been reported that the TraI protein encoded by plasmid F also has the cleaving and rejoining activities of the single-stranded DNA (Sherman & Matson 1994) which is similar to those encoded by the plasmids belonging to different incompatibility groups.…”
Section: Introductionmentioning
confidence: 99%